WAYS TO INCREASE THE EFFICIENCY OF AGRICULTURAL PRODUCTION - Narinbayeva Gulnora Karimovna; Zhalilov Shokhjakhon Kholbozor Ogli; Nurmukhammadov Islombek Oybek Ogli (American Journals, 2023)
The article discusses ways to improve the efficiency of agricultural production. In Uzbekistan, horticulture is one of the leading branches of agriculture and occupies a special place in providing the population with food.